Interfacial coupling effects in two-dimensional ordered arrays for microwave attenuation - Yijie Liu; Jintang Zhou; Chenchen Li; Henghui Zhang; Yucheng Wang; Yi Yan; Lvtong Duan; Zhenyu Cheng; Yao Ma; Zhengjun Yao (Nature Communications)
Abstract With the development of nanotechnology, nano-functional units of different dimensions, morphologies, and sizes exhibit the potential for efficient microwave absorption (MA) performance. However, the multi-unit coupling enhancement mechanism triggered by the alignment and orientation of nano-functional units has been neglected, hindering the further development of microwave absorbing materials (MAMs). In this paper, two typical ZIF-derived nanomaterials are self-assembled into two-dimensional ordered polyhedral superstructures by the simple ice template method. The nano-functional units exhibit distinctive dielectric-sensitive behaviors after self-assembling into two-dimensional ordered arrays. The modified 2D ordered polyhedral superstructures not only inherit the atomic-level doping and well-designed shell structure, but also further amplify the loss properties to realize the multi-scale modulated MA response. Satisfactory MA performance in C, X and Ku bands is finally achieved. In particular, the ultra-broadband microwave absorption bandwidth (EAB) of 6.41 GHz is realized at 1.82 mm thickness. Our work demonstrates the two-dimensional ordered array-induced multiscale polarization behavior, providing a direction to fully utilize the potential of wave-absorbing functional units.